Electronic Banking and Its Impact on Customer Satisfaction of Nepalese Commercial Banks - Guna Raj Chhetri (Pravaha, 2023)
Electronic Banking and its impact on customer satisfaction of Nepalese commercial banks explores the relationship between internet banking and customer satisfaction. Internet banking allows customers to conduct real-time banking transactions electronically, offering convenience and accessibility. Utilizing a descriptive and casual comparative research design, the study examines internet banking users across 20 commercial banks in Nepal, focusing on Nepal Investment Bank Limited, Nabil Bank Limited, and Himalayan Bank Limited. Through purposive sampling, 150 respondents were selected, with 50 from each bank, for primary data collection. The findings indicate high levels of satisfaction with online banking services, with respondents expressing agreement on various aspects such as ease of website navigation, meeting personal needs, and prompt service delivery. Correlation analysis reveals positive and significant relationships between customer satisfaction and key factors including efficiency, personal need fulfillment, reliability, responsiveness, site organization, and user friendliness. Finding suggest that a strong association between internet banking and customer satisfaction. These findings underscore the importance of internet banking in enhancing customer experience and satisfaction within the Nepalese commercial banking sector. Electronic banking and its impact on customer satisfaction of Nepalese commercial banks.